(3GdGfJbGA aj efGbH GdCFeI GdKdGKI GdabgGA (B( (3eGdc hGdTGaYi hCHh MfjaI (B)s - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Edg GdChdjf hGdBNQjf EdN s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B629 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B16 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs